2019
DOI: 10.1063/1.5108999
|View full text |Cite
|
Sign up to set email alerts
|

Compressed liquid marble ruptures at edge

Abstract: An improved understanding of the rupture dynamics for liquid marbles is essential for their application in sensors, miniaturized reactions, biomedical scaffolds, the synthesis of functional materials, and others. This work suggests that a compressed liquid marble always ruptures at the edge of the contact area between the marble and a substrate. The rupture dynamics of a compressed marble is visualized with a particle-level resolution using a marble coated with monodispersed microparticles. High-speed photogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The disintegration mechanism of the LMs against fall impact is important to understand the stability of the LMs. Recently, the Liu group studied the rupture dynamics of a LM compressed between two glass substrate and found that the rupture always occurred at the edge of the contact area between the LM and the glass substrate, regardless of defects formed on the LM surfaces . In our system, the LMs were compressed in a similar manner when they collided with the substrate, and we therefore expect that the LMs were disrupted by a similar mechanism upon impact with the underlying substrate.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The disintegration mechanism of the LMs against fall impact is important to understand the stability of the LMs. Recently, the Liu group studied the rupture dynamics of a LM compressed between two glass substrate and found that the rupture always occurred at the edge of the contact area between the LM and the glass substrate, regardless of defects formed on the LM surfaces . In our system, the LMs were compressed in a similar manner when they collided with the substrate, and we therefore expect that the LMs were disrupted by a similar mechanism upon impact with the underlying substrate.…”
Section: Resultsmentioning
confidence: 64%
“…Such particle systems would further allow correlating interfacial properties of the stabilizing particles with the resulting mechanical properties of the LM. There have been several attempts to fabricate monolayer-stabilized LMs. Liu et al investigated the mechanical properties of LM stabilized by a few tens micrometer-sized particles with different sizes . In their work, they found an increase in the critical pressure upon which the LM collapses for increasing diameters of the stabilizing particles.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical robustness of an LM measures the stability of the marble under high pressures, impacts, and physical deformations. The mechanical durability of the prepared LMs was investigated by dropping the marbles of volume 10 and 5 μL from different heights, and the corresponding information is shown in Videos S6 and S7. It was observed that the 5 μL LM bounces off after dropping from a height of 3.5 cm, whereas the 10 μL LM bounces off after dropping from a height of 2.5 cm, indicating the dependence of LM volume on the mechanical durability.…”
Section: Resultsmentioning
confidence: 99%
“…Solid particles coated on the liquid marbles make them resistant to compression and impact. 46 The elasticity and robustness of liquid marbles are the main factors to determine the stability of liquid marbles upon deformation, shocks, and impact. 47 In order to investigate the mechanical properties of sulfurstabilized liquid marbles, a 10 μL water droplet was rolled on the sulfur powder for 5 s, and then the prepared liquid marbles were compressed between two parallel plates until failure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Solid particles coated on the liquid marbles make them resistant to compression and impact . The elasticity and robustness of liquid marbles are the main factors to determine the stability of liquid marbles upon deformation, shocks, and impact .…”
Section: Resultsmentioning
confidence: 99%